ANALISIS PENGARUH KEBERAGAMAN PROGRAM WISATA, MUTU PROGRAM WISATA, DAN MUTU PELAYANAN TERHADAP KEPUASAN WISATAWAN DALAM MENINGKATKAN POSITIF WORDS OF MOUTH (Studi Pada Agrowisata Kebun Buah Plantera Fruit Paradise, Desa Sidokumpul, Kecamatan Patean, Kabupaten Kendal) - Irmanda, MC. Sukma (Master of Management Diponegoro University, 2012)
This research paper aims is to analyze the influence of programs variety, programs quality, service quality on tourist satisf action which increase positive words of mouth (WOM) communication. 100 respondents from Plantera Fruit Paradise Agrotourism were selected as sample. Sample are taken through accidental sampling technique. Data collection technique deployed was questionnaires and analyzed using multiple liner regression.The empirical result show that service quality, programs quality, and programs variety are positively and significantly related to tourist satisfaction and positive WOM. Service quality were the most influental factors on tourist satisfaction. Therefore, Plantera Fruit Paradise Agrotourism have to improve their service quality in many ways in order to increase tourist satisfaction and create positive WOMThis paper concludes that positive WOM and customer satisfaction can be enhanced if tourists got the best service quality from tour guide, and also their needs and expectations are considered during the design packages offered. This paper also provides the implications for theoritical and managerial and offer directions for future research.